La psicología de la imagen en el pensamiento de James Hillman - García Álvarez, César (Estudios humanísticos. Geografía, historia y arte, 2001)
The enormous transcendence that the American psychologist James Hillman gives to the image, as the basis of the human psychical life, invites to a theoretical and methodological reflection about its application to the field of the art's theory, and specially to the psychology of the image. Hillman's ideas may be applied to the interpretation of the history of art, and easily harmonised with the foundations of other theoretical frames. However, a critical analysis of the application that Hillman himself makes of his own method to the art and culture of the Italian Renaissance, reveals itself erroneous and contradictory in some aspects, which allow to check that the validity of Hillman's ideas as a method of historical analyse depends on a correct reading of the texts and documents of the times studied, the only ways of access to the knowledge and reconstruction of the contents of the Unconscious of a precise historical period.